Prevalence of multiple myeloma in patients on hemodialysis programs - David Garrido; Omar Seminario; Juan Santacruz; Evelyn Moreira; Rosalina Lituma; Jorge Moscoso; Ubelis Rosales; Alfonso Silva Contreras; Victor Hugo Ortega; Angel Quevedo; Franklin Mora-Bravo; Santiago Silva Tobar; et al. (REV SEN)
Introduction: Multiple myeloma (MM) is a hematological malignancy that often causes kidney failure, affecting more than 50% of MM patients. Kidney damage in MM is primarily due to cast nephropathy, light chain deposition disease, and amyloidosis. However, there are no data on MM patients undergoing hemodialysis in Ecuador. This study aims to report the prevalence of MM in the country's hemodialysis units.